A case report of anaplastic carcinoma with osteoclast-like giant cells arising in the pancreatic body. Issue 6 (25th June 2022) - Kitazono, Masaki; Fujita, Makoto; Ito, Ayaka; Oyama, Tomohiro; Ikeda, Naotaka; Eguchi, Mayumi; Sato, Rikiya; Uchiyama, Shuichiro; Toyosaki, Ryoichi; Yokomakura, Naoya; Suenaga, Toyokuni; Kusumoto, Hirotake; et al.
Abstract: The patient is a 58-year-old woman. She was referred to our hospital following a computed tomography scan that revealed a 2-cm tumor-like lesion in the pancreatic body. Endoscopic ultrasound fine-needle aspiration examination revealed a suspected undifferentiated carcinoma with pleomorphic type. The patient was diagnosed with anaplastic carcinoma of the pancreas (ACP) and underwent distal pancreatectomy with lymph nodes dissection. The resected body and tail of the pancreas had a nodular tumor measuring 30 mm in diameter. Histologically, the main lesion of the tumor showed well-differentiated adenocarcinoma, and diffuse proliferation of atypical short spindle cells and round cells accompanied by multinucleated giant cells aggregation was observed around the tubular structure; hence, it was diagnosed with ACP. The postoperative course was uneventful, and the patient was discharged 14 days after the operation. It has already been about 5 years since the surgery, and although the tumor has recurred, the patient is still alive and undergoing chemotherapy.